Satellites: Equation of Motion in Nechvill's Co-ordinate System - Sushil Chandra Karna (International Journal of Mathematics And its Applications, 2020)
This paper deals with the system of non-linear, non-autonomous and non-homogeneous equations of motion in terms of the Nechvill's Co-ordinate system have been derived. The general solution is beyond our reach.